1998
DOI: 10.1007/s005860050038
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic incidence: a fundamental pelvic parameter for three-dimensional regulation of spinal sagittal curves

Abstract: IntroductionSagittal spinal morphology varies from one individual to the another and is specific to each person. Classifications proposed in the literature are based on the measurements of curvatures, angulations or other parameters, chiefly for a normal population [1-3, 7, 11, 13, 15-17]. They are purely descriptive rather than in any way analytic.Modifications of sagittal spinal curvatures have been connected with changes in pelvic orientation [7,11,12,16,17]. Nevertheless, the role of pelvic anatomy in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
1,096
6
69

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,505 publications
(1,256 citation statements)
references
References 5 publications
40
1,096
6
69
Order By: Relevance
“…Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing. Decreasing values in lumbar lordosis and sacral slope angles in patients with DDD are consistent with the spine literature, where these sagittal parameters are used to evaluate individual sagittal balance [4,5,28]. Interestingly, similar to a previous study evaluating sagittal balance during standing in patients undergoing THA [24], some patients with DDD in our study had such excessive posterior pelvic tilt and lack of lumbar lordosis that they required knee flexion to adapt, because hip extension was insufficient.…”
Section: Discussionsupporting
confidence: 89%
“…Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing. Decreasing values in lumbar lordosis and sacral slope angles in patients with DDD are consistent with the spine literature, where these sagittal parameters are used to evaluate individual sagittal balance [4,5,28]. Interestingly, similar to a previous study evaluating sagittal balance during standing in patients undergoing THA [24], some patients with DDD in our study had such excessive posterior pelvic tilt and lack of lumbar lordosis that they required knee flexion to adapt, because hip extension was insufficient.…”
Section: Discussionsupporting
confidence: 89%
“…Pelvic incidence Angle subtended by a line which is drawn from the center of the femoral head to the midpoint of the sacral endplate and a line perpendicular to the sacral endplate [16]. Sacral slope The angle subtended by a horizontal reference line and the sacral endplate line.…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to have an optimal congruence between pelvic and spinal parameters to achieve an economic posture placing the axis of gravity in a physiologic position [3,5,14,17].…”
Section: Global Balance Evaluationmentioning
confidence: 99%